Rising to the Challenge of COVID-19: Pivoting to Online and Project-Based Physiotherapy Student Placements in Contemporary Professional Settings - Lawton, Vidya; Vaughan, Rebecca; Jones, Taryn M.; Pacey, Verity (International Journal of Practice-based Learning in Health and Social Care, 2021)
Online and project-based student placements in sport and corporate settings were incorporated within the Macquarie University Doctor of Physiotherapy following the restriction of face-to-face delivery during the COVID-19 pandemic. This study explores student and educator perceptions of these placements, and analyses student performance results to provide future recommendations. The mixed-methods design included a student survey, semi-structured educator interviews and quantitative analysis of student assessment performance comparing 2020 to 2018/2019 cohorts. Quantitative survey data were described, with proportional differences between groups analysed. Open-ended survey responses and interview transcripts were thematically analysed, and integration of all results was performed. Themes derived from 24 student surveys highlighted that the learning experiences and skills required for online and project-based placements were varied and valuable. Analysis of 176 students’ performance showed differences between performance and applicability of assessment items in 2020 placements in comparison to previous years, although all students met performance requirements. Analysis of eight educator interviews identified that online and project-based placements changed experiences for all stakeholders and highlighted the need for enhanced educator and student communication and organisation for the placement to be successful. Online and project-based placements were considered a better reflection of contemporary work practices, producing valuable deliverables to the business. Three final integrated themes were identified regarding online and project-based elements of placements: learning experiences of students differed, skills for students and educators differed, and placements were representative of real-world work. A hybrid approach that incorporates both online and onsite placement time and includes a project-based component is recommended for future placements. Project-based and online elements provide genuine and valuable learning opportunities for physiotherapy students in preparation for real-world work.